LINGUISTIC ANALYSIS OF METAPHORS AND COMBINATIONS IN WILLIAM SHAKESPEARE’S ROMEO AND JULIET - Hodiyeva , Marjona Olimjon qizi (Innovative Development in Educational Activities, 2023)
This article explores the use of metaphors and fixed conjunctions in William Shakespeare’s "Romeo and Juliet" through a linguistic analysis. The author examines how Shakespeare uses metaphors to convey complex emotions and relationships between characters in the play. The article also delves into the use of fixed conjunctions, such as "but" and "yet," to highlight contrasts and tensions within the text. By applying linguistic analysis to the play, the article offers insights into the nuances of Shakespeare’s language and its impact on the portrayal of characters and themes in "Romeo and Juliet."